Urinary D-Glucaric Acid Excretion in the Seveso Area, Polluted by Tetrachlorodibenzo-p-Dioxin (TCDD): Five Years of Experience - Idéo, G.; Bellati, G.; Bellobuono, A.; Bissanti, L. (Environmental health perspectives, 1985)
On July 10, 1976, an explosion in a factory in Seveso, Italy, located 30 km north of Milan, producing trichlorophenol caused the release of TCDD-containing compounds in the surrounding area. Since extremely small doses of TCDD have been shown to induce hepatic microsomal enzymes in animals, urinary D-glucaric acid excretion (a measurable index of enzyme induction), has been investigated in Seveso in adults and children 6 to 8 years old, in order to clarify whether levels of environmental exposure to TCDD were sufficient to produce an induction in man. Urine samples were collected from 1976 to 1981. As a control group, people living in Cannero (a nonindustrialized village on lake Magiore), in Busto Arsizio (a small industrial town near Milan) and in Lentate (a noncontaminated zone near Seveso) were chosen. In the first period of collection, children with chloracne (which is considered to be a characteristic manifestation of intoxication with chlorinated products) showed significantly increased levels of D-glucaric acid excretion compared to children without chloracne living in the same zone. As far as chronic exposure is concerned, up to 3 years after the accident both adults and children living in the Seveso area showed a statistically significant enhancement of D-glucaric acid elimination compared to the control groups. This study demonstrates that adults and children living in the polluted zones had an increased activity of hepatic microsomal enzymes for some years, since, although the urinary excretion of D-glucaric acid is only an indirect measure of enzyme activity, studies in man have indicated that it is, however, sensitive and quantitative. As far as the cause of this enhancement is concerned, since at least in children it is possible to exclude the influence of alcohol, contraceptives or other drugs, it is reasonable to conclude that tetrachlorodibenzo-p-dioxin (TCDD), an inducing agent, could be responsible for this phenomenon.